Ekotoksikologija: navodila za vaje - Vončina, Bojana; Volmajer Valh, Julija; Vajnhandl, Simona (2017)
Ecotoxicology: Instructions for Laboratory Work. Environmental pollution with various xenobiotic substances that with their bioactive activity can negatively affect the ecosystem and all its constituent elements is one of the main problems in the last decades. Ecotoxicology is a science dealing with evaluation and understanding of the acute and chronic action of these substances on living organisms. For this purpose, we use different standardized and non-standardized toxicity tests (Daphnia Magna, Vibrio Fischeri, Allium test, yeast toxicity test). Instructions for laboratory work cover some basic toxicity tests. With their implementation, students will learn about the limitations, strengths and weaknesses of individual tests and develop critical evaluation of results.
Keywords: ecotoxicology; toxicity; toxicity tests; Daphnia Magna; Vibrio Fischeri